REORGANIZATION OF HIGHER EDUCATION THROUGH THE EYES LECTURERS: STUDY RESULTS - Svetlana B. Seryakova; Lyudmila F. Krasinskaya (Moscow Polytechnic University, 2022)
The article shows the results of the opinion poll of university lecturers. The survey was aimed to reveal their attitude towards reorganization of higher education. There is presented the analysis of their opinion on restructurization of ineffective universities, the appearance of leading universities, implementation of level training system and competence-oriented educational standards etc. Special attention is paid to the problem of reform efficiency, and to the factors negatively influencing modernization of higher school.